Smart snack module using peer learning to improve biological science literacy - Yahmi Setyaningrum; Irma Wulandari; Ratih Septiasari (Biosfer: Jurnal Pendidikan Biologi, 2026)
Non-communicable diseases (NCDs) and adolescent malnutrition remain significant public health challenges, particularly among school-aged populations. Unhealthy snacking behaviors, combined with limited science literacy, reduce adolescents’ ability to make informed dietary decisions, underscoring the urgent need for effective, school-based educational interventions. This study aimed to develop and assess the effectiveness of a Smart Snack Strategy e-module that integrates peer education and problem-based learning (PBL) to enhance science literacy. The research used a Research and Development (R&D) approach with the ADDIE model, comprising needs analysis through health screening and stakeholder consultation, followed by design, development, expert validation, and product trials. The e-module covers three main topics: the smart snack concept, basic food microbiology, and food label reading. Validation by content, language, media, and learning experts confirmed that the module is highly feasible in terms of quality and usability. Subsequent limited and broader trials with 25 students demonstrated a significant improvement in science literacy, with an average gain of 30.92 points (p < 0.05). The e-module also fostered greater motivation, problem-solving skills, and healthier snack decision-making. These findings indicate that integrating peer education and PBL is effective in promoting active learning and healthy lifestyle behaviors. Therefore, the Smart Snack Strategy e-module represents a viable and innovative medium for enhancing science literacy and supporting adolescent health promotion in school settings.